Electromagnetic Form Factors for 7,9,11Be Isotopes with Exact Center of Mass Correction - Hawi, M. H.; Dakhil, Z. A. (Iraqi Journal of Science, 2022)
The shell model calculations with Cohen-Kurath (C-K) interaction were carried out to investigate form factors of elastic transverse electron scattering, and magnetic dipole-moments of odd 7,9,11Be isotopes. The effect of the exact value of center of mass correction was adopted to generate the magnetic form factors in Born approximation picture. The contribution of the higher 2p-shell configuration was included to reproduce the experimental data. A significant improvement was obtained in the present results with core-polarization (CP) effect through the effective g-factors. The occupancies percentage with respect to the valence nucleons was also calculated.